The reality of religious tourism publications design and ways of developing The upper threshold model: صادق هاشم حسن الموسوي (Al-Academy, 2016)
Tourism is one of the most important sources of income of economic key countries in the world so are imports of tourism for some countries a source of income is not significant of the total revenues of States. Making those countries, and those countries a destination for visitors, and here should be interest in the Wealth and cultural heritage that distinguishes Islamic countries in general, and Iraq in particular, must be placed specialist studies in all areas for the development of this area of tourism, especially religious tourism to achieve a desired and desired of such research.It is the most important ways to develop tourism in general and religious tourism is of particular publications, advertising, and is important for us in this research is the announcement and the publication containing the subject of research (and the reality of design prints of religious tourism and ways of development). Researcher select the problem purely by asking the followingIs designed publications of religious tourism in the upper threshold according to the foundations and rules of design.He then discussed the researcher the importance of his research by finding the link state between the announcement and tourism, Vllaalan effects active through the mechanisms of speech, or so-called means of expression different that pass a message to the recipient of "The Declaration and publications play a big role aspires through the definition of the public on a particular subject cares about designer building the request by the institution or may be thedesigner is from Find this search to his sense that the search can be a research framework for cognitive strengthens and the advertising and publication layout is used in religious tourism. has shed light on a lot of internal and external variables and the pose of the impacts on the structure design advertising and printing the publication of religious tourismThe current research aims to 1.Definition and design of the reality of religious tourism publications issued by the upper threshold disinfectant2.Submit proposals for the purposes of theory development and design of the reality of religious tourism publicationsThe limits set by the research scholar with the followingA. Reduction objective: the theme of religious tourism publications design used in the upper threshold cleansedB. Reducing the spatial: the upper kindergarten holy. Holy city of NajafC. Temporal limitation: the calendar year from 01.01.2011 to 01.01.2012The researcher dealt with in the second quarter in light of the theoretical framework and previous studies to a number of themes areFirst research: Design and print advertisingThe second topic: the aesthetic and functional dimensionPublications and advertisements of religious and touristThe third topic: advertising and printed means of communicationSection IV: History of the upper threshold cleansed and history publications, including travelersIdentified in Chapter III through fares purely on that he chose a descriptive approach in the field of scientific research and the sample intentionality through the selection of form analysis research (testing tool), and then was resolved the samples in the process of research and came out a researcher from the set of results that put through a total of recommendations and proposals of the next above